Advertisement calls of anuran amphibians from Itinguçu State Park—Peruíbe municipality, São Paulo state, Brazil - Barroso, Livia Zanuzzi; Velasco, Isabel Gonzalves; Nunes, Ivan (Zootaxa, 2026)
In anurans, acoustic communication is essential for reproduction, territorial defense, and social interactions. The advertisement call plays a central role in mate attraction and species recognition, making it a key trait in taxonomic and ecological studies. This study aims to review and update the acoustic features of the advertisement calls of seven species recorded within the Itinguçu State Park, located in the Atlantic Forest of São Paulo, Brazil. We compared our results to existing data available in literature. Recordings were made during fieldwork from April 2022 to February 2023, combining passive acoustic monitoring and active searches. Acoustic data were analyzed in the software Raven Pro 1.5. We reviewed calls from seven species distributed across four families: Bufonidae, Hylidae, Hylodidae and Phyllomedusidae. Our results include the definition of sound type for all species recorded, providing temporal and spectral parameters for each species. Most results aligned with existing data, although we report updates for the dominant frequency of Hylodes dactylocinus, and new information on the call duration and pulse number of Scinax perereca. Additionally, we compared the acoustic parameters obtained via passive and active sampling methods using principal component analysis (PCA). This study on acoustic data variation across different regions aids in taxonomic identification and ecological studies, as different behavioural and acoustic pressures exist in different localities.